Life Skills in Education in the Smart Society 5.0 Era - Muis, Abdul; Nasruddin, Nasruddin; Suparman, Suparman (JUPE : Jurnal Pendidikan Mandala, 2023)
The development of information and communication technology occurs very quickly and can bring changes in society. Currently the development of technology and industry has reached society 5.0 and as we know, education today is centered on balance, where the internet is not only a medium of information but plays a role in living life. The formulation of the problem in this study is about the understanding and role of   society 5.0, as well as concepts and attitudes in learning in the era of society 5.0. The research method used is qualitative description with literature study. The conclusion of this study is that technological developments cannot be avoided, so we must be able to adapt and respond to these developments.